Secretory and transcriptomic responses of mantle cells to low pH in the Pacific oyster (Crassostrea gigas) - Zúñiga-Soto, Nicolás; Pinto-Borguero, Ingrid; Quevedo, Claudio; Aguilera, Felipe (Frontiers in Marine Science, 2023)
Since the Industrial Revolution, the concentration of atmospheric carbon dioxide (CO2) due to anthropogenic activities has increased at unprecedented rates. One-third of the atmospheric anthropogenic CO2 emissions are dissolved in the oceans affecting the chemical equilibrium of seawater, which in turn leads to a decrease in pH and carbonate ion (CO32-) concentration, a phenomenon known as ocean acidification (OA). This chemical disequilibrium can be detrimental to marine organisms (e.g., mollusks) that fabricate mineralized structures based on calcium carbonate (CaCO3). Most studies on the effect of reduced pH in seawater have been conducted on the early developmental stages of shell-building invertebrates, given less attention to how adult individuals face OA stress. Here, we evaluate histological, secretory, and transcriptional changes in the mantle of adult oysters (Crassostrea gigas) exposure to ambient (8.0 ± 0.2) and reduced (7.6 ± 0.2) pH during 20 days. Most histological observations did not show differences in terms of mantle cell morphology. However, Alcian Blue/PAS staining revealed significant differences in the number of Alcian Blue positive cells in the mantle edge, suggesting a decrease in the secretory activity in this morphogenetic zone. Transcriptomic analysis revealed 172 differentially expressed genes (DEGs) between mantle tissues from adult oysters kept in normal and reduced pH conditions. Almost 18% of the DEGs encode secreted proteins that are likely to be contributing to shell fabrication and patterning. 17 of 31 DEGs encoding secreted proteins correspond to oyster-specific genes, highlighting the fact that molluscan shell formation is underpinned by a rapidly evolving secretome. The GO analysis of DEGs encoding secreted proteins showed that they are involved in the cellular response to stimulus, response to stress, protein binding, and ion binding, suggesting these biological processes and molecular functions are altered by OA. This study demonstrates that histology and gene expression profiling can advance our understanding of the cellular and molecular mechanisms underlying adult oyster tolerance to low pH conditions.